No more reason for ignoring gelatinous zooplankton in ecosystem assessment and marine management: Concrete cost-effective methodology during routine fishery trawl surveys. (February 2018) - Aubert, A.; Antajan, E.; Lynam, C.; Pitois, S.; Pliru, A.; Vaz, S.; Thibault, D.
Abstract: Gelatinous zooplankton, including cnidarians, ctenophores, and tunicates (appendicularians, pyrosomes, salps and doliolids), are often overlooked by scientific studies, ecosystem assessments and at a management level. Despite the important economic consequences that they can have on human activities and on the marine food-web, arguments often related to the costs of monitoring or their coordination, or simply negligence, have resulted in the absence of relevant monitoring programs. A cost-effective protocol has been applied on trawling from existing fishery surveys conducted by national laboratories in England and France. The testing phase has successfully demonstrated the adequacy of such a tool to sample macro- and mega-zooplankton gelatinous organisms in a cost-effective way. This success has led to the acceptance of this protocol into the French implementation of the EU's Marine Strategy Framework Directive (MSFD). Here, a protocol which can be applied to any trawl-based fishery survey and in any new large-scale monitoring program is provided. As an ecosystem approach to marine management is currently adopted, exemplified by the MSFD in Europe, gelatinous zooplankton should be monitored correctly to prevent a knowledge gap and bias to ecosystem assessments in future. Highlights: There is a clear gap in the monitoring of macro- and mega- gelatinous zooplankton. A cost-efficient method taking advantage of fish trawling has been successfully tested. A step by step protocol to record the bycatch of gelatinous zooplankton is provided here. Gelatinous zooplankton should be considered in ecosystem based marine management.